Pengaruh Kecerdasan Spiritual terhadap Krisis Makna Peserta Didik SMP pada Era Digital di Kota Payakumbuh - Angga Ramadhan; Oten Novita; Alfi Rahmi (YASIN, 2026)
Although the crisis of meaning among students has received increasing attention alongside developments in the digital era, studies that specifically analyze the effect of spiritual intelligence on the crisis of meaning among junior high school students from the perspective of Islamic Religious Education remain limited. This study aims to analyze the effect of spiritual intelligence on the crisis of meaning among junior high school students in Payakumbuh City. This study used a quantitative approach with an explanatory survey design, involving 36 students selected through a probability sampling technique. Data were collected using a Likert-scale questionnaire measuring spiritual intelligence and the crisis of meaning. The research instrument was tested for validity and reliability, while the data were analyzed using descriptive statistics and simple linear regression with the assistance of IBM SPSS Statistics. The results show that the students’ level of spiritual intelligence was in the high category, while their level of crisis of meaning was in the low to moderate category. The results of hypothesis testing show that spiritual intelligence affects the crisis of meaning; the higher the students’ spiritual intelligence, the lower their tendency to experience a crisis of meaning. This finding strengthens studies on the role of spiritual intelligence as a protective factor in shaping students’ meaningfulness in life. The conclusion of this study affirms the importance of strengthening spiritual intelligence through Islamic Religious Education learning to support students’ mental health, character formation, and meaningfulness in life in the digital era. The implications of this study include theoretical contributions to the development of Islamic Religious Education literature and practical implications for schools in designing learning that strengthens students’ spiritual dimensions. Keywords: Spiritual Intelligence; Crisis of Meaning; Junior High School Students; Islamic Religious Education; Digital Era